RESEARCH OF THE PROCESS OF HYDRATION OF ROSA MAJALIS - K. N. Nitievskaya (Современная наука и инновации)
The article presents theoretical data on the biochemical compounds of Rosa majalis that are of interest in the development of products based on it. Rosa majalis are characterized by a high content of biologically active compounds and have antioxidant, anti-mutagenic and anti-carcinogenic effects. The purpose of the study is to study the hydration of Rosa majalis in General and crushed form for the development of basic principles in various processing modes. Macroscopic analysis of dried Rosa majalis in General and crushed fruit was performed. The fractional composition of crushed Rosa majalis was studied. The process of hydration of Rosa majalis under various parameters is analyzed. Pre-preparation of Rosa majalis, taking into account the temperature parameters and duration, allows you to determine the features of technological processes for seed treatment. The fruit grinding process allows you to analyze further parameters of fruit processing when developing products based on Rosa majalis. To evaluate the technological parameters, a swelling coefficient was introduced to calculate the amount of water in the process of technological processing. Illustrations of changes in the color intensity of non-hydrated water fraction when using water in different temperature parameters (60 and 20+ 2°C) and duration (30-150 minutes) are given. The data on the study are summarized, the principles of further processing of Rosa majalis are formed, including recommendations on the temperature treatment modes, as well as the water ratio when developing a food product recipe.